Disparities in Disruptions to Postsecondary Education Plans During the COVID-19 Pandemic - Ran Liu (SAGE Publishing, 2021)
This study examines disruptions to postsecondary education plans in the United States during the COVID-19 pandemic. Using nationally representative data from the U.S. Census Bureau's Household Pulse Survey from August 2020 through March 2021, we investigate the prevalence, forms, reasons, and disparities of education disruption across different sociodemographic groups. While nearly three in four households report education plan disruption, the forms and reasons are drastically different. Black and Latinx respondents are more likely to report plan cancellation, while Whites are more likely to report taking classes in different formats. Non-White groups are more likely to cancel plans due to health or financial concerns, while Whites are more likely to cancel plans due to concerns about changes to campus life. Results also reveal nuanced intersections of race, type of education plans, and household vulnerability in affecting education disruption, pointing to the necessity of well-targeted initiatives to address long-term consequences and resulting inequality.